Artificial Intelligence and Qur’anic Interpretation for the Visually Impaired Through the Nurul Application - Zerlinda Prasanti Supranggono; Aisyah Ramadhani Anshory; Siti Nafisatul Qurba (Yayasan Pesantren Mahasiswa An-Nur, 2025)
The rapid advancement of technology offers new opportunities to improve human life, particularly in education. However, many individuals with visual impairments still face barriers in accessing technological tools, especially for learning and interpreting the Qur’an. The Nurul application, an AI-based innovation, was developed to assist blind individuals in Indonesia in enhancing independence and improving Qur’anic learning, particularly in understanding tafsir (interpretation). This study aims to describe the role of the Nurul application in supporting Qur’anic and tafsir learning among blind students at SLB A YPAB Surabaya, to examine how its features improve accessibility, and to evaluate the validity of its Qur’anic interpretations. Using a descriptive qualitative approach, data were collected through interviews, observations, documentation, and literature review. The analysis employed intertextual theory to assess the accuracy of the tafsir content. Findings reveal that Nurul provides interactive, user-friendly features that effectively support blind users in religious education. Key functions, such as Qur’an mode, Magic Mirror, and facial expression reader, help students engage with learning more independently and meaningfully. Observations and interviews indicate that the application effectively aids users in understanding Qur’anic verses and interpretations with sufficient accuracy. However, further improvements are needed to enhance tafsir validity and overall usability. This study contributes to the advancement of AI-based educational technology that promotes inclusivity in religious learning for the visually impaired.